Severe drug‐induced anaphylaxis: analysis of 333 cases recorded by the Allergy Vigilance Network from 2002 to 2010. Issue 7 (6th June 2013) - Renaudin, J.‐M.; Beaudouin, E.; Ponvert, C.; Demoly, P.; Moneret‐Vautrin, D.‐A.
Abstract: Background: A few series of well‐documented cases of severe drug‐induced anaphylaxis (SDA) are available. Methods: Cases collected by the Allergy Vigilance Network from 2002 to 2010 were analyzed for clinical signs, causative drugs, and efficacy of a stepwise approach to diagnosis, using skin tests, laboratory tests, and oral challenges. Results: Three hundred and thirty‐three cases concerned 300 adults (90.1%) and 33 children (9.9%): 206 females (61.9%) and 127 males (38.1%). Mean age was 42.7 ± 18 years. Anaphylactic shock (76.6%), severe systemic reactions (10.5%), acute laryngeal edema (9%), severe bronchospasm (2.1%), and six fatal cases (1.8%) were recorded. There were 270 cases (81.1%) of ambulatory anaphylaxis. Sixty‐three cases (18.9%) occurred during anesthesia. Hospitalization was required in 94.8% of cases. 23.7% of patients were admitted to an intensive care unit. Epinephrine was used in 57.9% of cases. Eighty‐four drugs were incriminated: antibiotics (49.6%), muscle relaxants, latex and anesthetics (15%), nonsteroidal anti‐inflammatory drugs (10.2%), acetaminophen (3.9%), iodinated or magnetic resonance imaging contrast media (4.2%), immunotherapy and vaccines (3.9%), and other drugs (13%). Among antibiotics, amoxicillin (97 cases), other penicillins (four cases), cephalosporins (41 cases), quinolones (15 cases), and pristinamycin (seven cases) were the most common. The diagnosis of drug hypersensitivity was obtained by skin tests in 72.9%, laboratory tests only in 2.4% of cases, and oral challenges (OCs) only in 3.9% of cases. Conclusions: Three hundred and thirty‐three case reports provided data on drugs involved in severe anaphylaxis. The efficacy of skin tests and poor use of laboratory tests are underlined. Further progress may depend on OCs.